Clinicopathological characteristics and prognostic analysis of breast cancer with a hormone receptor status of ER(-)/PR(+) - Wang, Xinli; Xue, Yan (Frontiers in Endocrinology, 2023)
Background It is unknown whether ER(-)/PR(+) breast cancer is an independent breast cancer subtype, how it differs from other subtypes, and what its significance is regarding treatment and prognosis. This study compared ER(-)/PR(+) breast cancer with other subtypes to better understand the biological characteristics and prognosis of ER(-)/PR(+) breast cancer, to guide clinical treatment and establish a theoretical foundation. Methods We retrospectively analyzed data for patients diagnosed with breast cancer in the Surveillance, Epidemiology, and End Results (SEER) database. The clinicopathological characteristics of ER(-)/PR(+) breast cancer, including age, tumor size, lymph node status, HER-2 status, pathological type and histological grade, were compared with other types of breast cancer. A risk scoring system was developed based on independent risk factors influencing prognosis to predict the patient’s prognosis, and a nomogram model was created to predict the patient’s survival rate. Receiver operating characteristic curve (ROC) and calibration curve was used to evaluate the predictive performance of the nomogram. Results The rates of T3-4, lymph node positivity, HER-2 positivity, infiltrating non-special pathological type, and G3 were significantly higher in ER(-)/PR(+) than in ER(+)/PR(+) cancer (p <0.001). ER(-)/PR(+) was similar to biological activity of ER(-)/PR(-) type. ER(-)/PR(+)/HER-2(+) patients had a better survival prognosis than ER(-)/PR(+) HER-2(-) patients (p<0.05). The prognosis of ER-/PR+ breast cancer was significantly associated with age, HER-2 status, and T stage. Conclusion ER(-)/PR(+) breast cancer is more similar to ER(-)/PR(-) breast cancer than other breast cancer subtypes, with an early age of onset, a high proportion of infiltrating non-special types, a high histological grade, and a high HER-2 positivity rate. Whether HER-2 positivity can improve the prognosis of ER(-)/PR(+)breast cancer is worth further discussion. The risk scoring system we developed can effectively distinguish between high-risk and low-risk patients. The nomogram we created had a concordance index of 0.736, and the calibration curve showed good agreement between the predicted and observed outcomes.